Growth inhibition of Mucuna bracteata by difeconazole / Noraasyikin Saufi - Saufi, Noraasyikin (Faculty of Plantation and Agrotechnology, 2015)
This study was carried out to determine the growth response of Mucuna bracteata towards the application of difenoconazole (DFZ) in attempts to control its excessive growth. In this project, M. bracteate was sprayed with different concentrations of DFZ, i.e. 0 (control), 100, 200, 300 and 400 mg/l. Experiment was carried out based on a complete randomized design (CRD) with five replicates. The data observed in this project were internode length to describe the potential vine extension, vine diameter, leaf area and relative chlorophyll content of the first fully developed leaf. The number of branches at the node with first fully developed leaves was also recorded as indicator of plant compactness. Data were collected weekly for a period of eight weeks after application of DFZ. All data were analyzed using SPSS software. Analysis of variance (ANOYA) was carried out. Treatment means were compared using Tukey's Honestly Significant Difference (HSD) Test at 5% level of significance. The results from this study showed that treatment with 400 mg/l DFZ generally resulted in significant growth inhibition in M. bracteata on clay loam.